Inflammatory markers and lipid profiles in obese children - Aidah Juliaty; Dina Kurniasih (Indonesian Pediatric Society, 2021)
Background Over 340 million children and adolescents aged 5-19 were overweight or obese in the year 2016. Individuals with obesity are at risk for metabolic disorders and lipid abnormalities. Adipose tissue is a major source of pro-inflammatory cytokines. Objective To evaluate possible correlations between inflammatory markers IL-6, TNFa, and hs-CRP with lipid profiles between obese and non obese children. Methods Eighty children, aged 13 to 15 years, were enrolled in this study (40 normoweight and 40 obese). All participants’s ( obese and normoweight children) total plasma cholesterol, HDL cholesterol, triglycerides, as well as circulating levels of inflammatory factors, such as TNF-α, IL-6, and high sensitivity-C-reactive protein (hs-CRP) level were measured. Results Obese children had significantly higher triglycerides (TG) and cholesterol, as well as lower HDL than normoweight subjects. Mean LDL levels were not significantly different between groups. The IL-6, TNFa, hs-CRP levels were significantly positively correlated with waist circumference. Analysis of the 4 blood lipid parameters and 3 inflammatory markers revealed significant positive correlations of triglycerides to TNFa and hs-CRP. In addition, HDL had significant negative correlations to both TNFa and hs-CRP. No correlations were found between IL-6 and the 4 lipid parameters, nor between TNFa or hs-CRP to LDL and cholesterol. Multivariate regression analysis revealed a significant association between weight-height ratio with hs-CRP (R2 0.118; 95%CI 1.65 to 191; P=0.046). Obesity is associated with adverse lipid and inflammations markers in children. Conclusion Obesity was associated with higher TG, cholesterol, TNF, and hs-CRP levels, as well as lower HDL.